Surgical Management of Recurrent Cervico-Vaginal Prolapse by Ovario-Hysterectomy in Stray Cows: A Report of 12 Cases - Borakhatariya, Devasee; Gadara , Arvind; Kasundra , Arjun (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
Pre and postpartum genital prolapse in cows is often a chronic and recurrent condition. Cervico vaginal prolapse is a very painful and serious condition due to which most of the animals undergo severe straining and may become recumbent. It is assumed that the occurrence of prolapse has a genetic predisposition in both cattle and sheep. It is regarded as an emergency condition and should be managed before excessive oedema, mucosal trauma, contamination and fatal haemorrhage lead to a grave prognosis. Genital prolapse is a major reproductive disorder in cattle and buffaloes (Mishra, 1998). Multigravidas are more often involved than heifers. Some cows with extreme laxity of the perineum and vulva may prolapse immediately after calving. The hormonal changes that occur during the last trimester of pregnancy especially increase estrogen and relaxin cause relaxation of the pelvic ligaments and surrounding soft tissue structures (Wolfe, 2009). However, chronic recurrent prolapse is due to the tenesmus as a result of the trauma/inflammation of the exposed part or due to cervicitis and/ or vaginitis. The prognosis depends upon the type of case, the duration of the exposure of the prolapsed mass and the degree of trauma inflicted upon the prolapsed mass. Good prognosis can be achieved if case is attended by professional assistance within two to five hours. Such cases can be treated by many methods like application of rope truss, purse string suture, Buhner’s technique, vulvoplasty, cervical fixation and modified Minchev method of fixation of perivagainal tissue (Kumar, 2005). Cases in which there has been delay and in which the endometrium is grossly contaminated and deeply congested, prognosis is guarded. Thus, amputation of the everted organ should be considered in such cases when injury is gross and resolution is impossible (Mahida, 2008). The present communication reports cases of forth degree cervico-vaginal prolapse with laceration, oedema and severe damage of prolapsed portion for more than 15 days with no chances of resolution that were managed by per vaginum ovario-hysterectomy.